2022
DOI: 10.1088/1742-6596/2265/2/022043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-induced gravity waves on finite wind-farm operations using a large-eddy simulation framework

Abstract: In the present study, we use large-eddy simulation (LES) to investigate how a capping inversion in combination with a stable free atmosphere influences the flow development and energy extraction in a large finite wind farm with a staggered and aligned layout. In the conventionally neutral boundary layer (CNBL), we find that gravity waves induce an unfavourable pressure gradient in the induction region of the farm which contributes to the upstream blockage, decreasing the available energy for first-row turbines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…This is a strong assumption, and in reality, this would depend on the atmospheric conditions. The LES results of Wu & Porté-Agel (2017) and Lanzilao & Meyers (2022) show approximately equal and opposite pressure changes at the front and rear of the farm, suggesting that this approximation is valid. However, the LES of Allaerts & Meyers (2017) and Lanzilao & Meyers (2023) suggest that this assumption is likely to be valid only for certain atmospheric stratifications.…”
Section: Momentum Availability Factor Modelmentioning
confidence: 95%
See 3 more Smart Citations
“…This is a strong assumption, and in reality, this would depend on the atmospheric conditions. The LES results of Wu & Porté-Agel (2017) and Lanzilao & Meyers (2022) show approximately equal and opposite pressure changes at the front and rear of the farm, suggesting that this approximation is valid. However, the LES of Allaerts & Meyers (2017) and Lanzilao & Meyers (2023) suggest that this assumption is likely to be valid only for certain atmospheric stratifications.…”
Section: Momentum Availability Factor Modelmentioning
confidence: 95%
“…The LES results in the literature have shown that large wind farms can induce additional pressure gradients across them (e.g. Allaerts & Meyers 2017; Wu & Porté-Agel 2017; Lanzilao & Meyers 2022). When farms induce additional pressure gradients, commonly a velocity reduction at the front of the farm is observed.…”
Section: Momentum Availability Factor Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…With LES all relevant processes such as turbulent entrainment of energy or Coriolis effects are modeled. Many wind farm LES studies have been performed in recent years, e.g., Allaerts and Meyers (2017), Wu and Porté-Agel (2017), Zhang et al (2019), Centurelli et al (2021), Lanzilao and Meyers (2022) and Maas and Raasch (2022). They show that complex flow phenomenon like inversion layer displacement, gravity wave induced pressure gradients, flow blockage and Coriolis force related wind direction changes can occur for large wind farms.…”
Section: Introductionmentioning
confidence: 99%